The effects of MS-10 dietary supplement, mixture of Korean thistle and thyme extracts, on bone health, and symptoms in menopausal women. (January 2019) - Noh, Yoo-Hun; Cheon, Seungui; Kim, In Hye; Lee, Seungah; Yin, XingFu; Jeong, JaeHun; Lee, Hongyeol; Ahn, Jae Hyung; Han, Seung Su; Bae, Yoojung; Jung, Yoonhee; Lee, WonBok
Graphical abstract: Highlights: MS-10 could modulate expression of genes that regulate proliferation in SaOS-2 cells. MS-10 could regulate bone health related factors in SaOS-2 cells and clinical study. Menopausal symptoms were improved by treatment of MS-10 in MENQOL test. MS-10 is natural drug for menopausal symptoms with bone health, without side effects. Abstract: In menopausal women, estrogen deficiency closely affects bone health. Previous studies report that MS-10, a combined extract of Cirsium japonicum and Thymus vulgaris, increases the efficiency of estrogen by activating the estrogen receptor. Here, the ability of MS-10 to enhance bone health and quality of life in women with menopausal symptoms was tested. Treatment with MS-10 induced alterations in the gene expression profile related with bone health of SaOS-2 osteoblast-like cells. MS-10 increased alkaline phosphatase (ALP) activity and osteocalcin, and reduced tartrate-resistant acid phosphatase (TRACP) activity in osteoblast-like cells. A clinical study showed that treatment with MS-10 (500 mg/day for 3 months) led to a significant decrease in ALP and osteocalcin levels. Also, women's scores on the Menopause-Specific Quality of Life questionnaire that takes into account vasomotor, psychosocial, physical, and sexual health, improved by 18.8%. In conclusion, the herbal material MS-10 may improve menopausal symptoms, including bone health.